PENGARUH SIKAP DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN PT. PRIORITAS KOTA BENGKULU - Putri Mayang Sari; Sri Ekowati; Meilaty Finthariasari (UM. Bengkulu, 2020)
This study aimed to determine The Effect of Attitude and Dicipline toward Employees’ Achievement of PT. Prioritas of Bengkulu City. The number of samples were used as many as 90 Respondents by using purposive sampling techniques. The data were analyzed by using Multiple Linear Regression Analysis Techniques, Determination Coefficient Analysis (R2), and Partial Test (t Test), Simultaneous Test (Test f).The results of this study indicate that partially significant attitudes influence work performance with a value of α = 0.00 and work discipline significantly influence work performance with a value of α = 0.11. While f Attitude Test (X1) and Discipline (X2) have a significant influence toward employees’ performance (Y) at PT. Prioritas Bengkulu City overall significant level of α = 0.000. It has a regression equation Y = 5.380 0.490 (X1) 0.317 (X2),with the coefficient of determination of the Adjusted R Square value is 0.423. The coefficient of determination has the meaning that together attitudes and discipline contribute in influencing work performance of employees of PT. Prioritas Bengkulu City. While the most dominant factor with the greatest regression coefficient value is a variable with a value = 0.490. Keywords: Attitude, Discipline and Work Performance of Employees.